Immunopathophysiology of inflammatory bowel disease: how genetics link barrier dysfunction and innate immunity to inflammation. Issue 6 (August 2017) - Mehta, Minesh; Ahmed, Shifat; Dryden, Gerald
Inflammatory bowel diseases (IBD) comprise a distinct set of clinical symptoms resulting from chronic or relapsing immune activation and corresponding inflammation within the gastrointestinal (GI) tract. Diverse genetic mutations, encoding important aspects of innate immunity and mucosal homeostasis, combine with environmental triggers to create inappropriate, sustained inflammatory responses. Recently, significant advances have been made in understanding the interplay of the intestinal epithelium, mucosal immune system, and commensal bacteria as a foundation of the pathogenesis of inflammatory bowel disease. Complex interactions between specialized intestinal epithelial cells and mucosal immune cells determine different outcomes based on the environmental input: the development of tolerance in the presence of commensal bacterial or the promotion of inflammation upon recognition of pathogenic organisms. This article reviews key genetic abnormalities involved in inflammatory and homeostatic pathways that enhance susceptibility to immune dysregulation and combine with environmental triggers to trigger the development of chronic intestinal inflammation and IBD.